The impact of digital literacy on learning outcomes among college students: the mediating effect of digital atmosphere, self-efficacy for digital technology and digital learning - Yuan, Ningbo; Yu, Qiuhui; Liu, Weiyu (Frontiers in Education, 2025)
Few studies have explored the specific internal mechanisms and links by which digital literacy impacts learning outcomes. This study investigates the complex relationship between digital literacy and learning outcomes among college students, using social cognitive theory (SCT) and structural equation modeling (SEM) as theoretical frameworks. Data were collected from 589 college students in China’s northwest region. The results reveal that digital literacy affected learning outcomes indirectly through the digital atmosphere, self-efficacy for digital technology, and digital learning. Specifically, digital atmosphere and digital learning mediate the relationship between digital literacy and learning outcomes. Self-efficacy for digital technology and digital learning jointly mediate the relationship between digital literacy and learning outcomes. Digital literacy has a positive and significant impact on the digital atmosphere and influences students’ self-efficacy for digital technology, thereby motivating them to participate in digital learning and ultimately having a positive impact on learning outcomes. Overall, the findings highlight the importance of developing digital literacy, optimizing digital learning atmospheres, and enhancing self-efficacy to fully leverage undergraduates’ learning potential in the digital age.